2012
DOI: 10.1017/s1473550412000377
|View full text |Cite
|
Sign up to set email alerts
|

Life's chirality from prebiotic environments

Abstract: A key open question in the study of life is the origin of biomolecular homochirality: almost every life-form on Earth has exclusively levorotary amino acids and dextrorotary sugars. Will the same handedness be preferred if life is found elsewhere? We review some of the pertinent literature and discuss recent results suggesting that life's homochirality resulted from sequential chiral symmetry breaking triggered by environmental events. In one scenario, autocatalytic prebiotic reactions undergo stochastic fluct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 85 publications
(197 reference statements)
1
9
0
Order By: Relevance
“…Proposed mechanisms that might yield compounds in significant enantiomeric excess (e.g., differential photolysis by circularly polarized starlight [DMMN + 11], the growth and dissolution of chiral crystals [NIM + 08], or hypothetical autocatalytic cycles [GW12]) are of dubious prebiotic realism [ÁBC + 10], while prebiotic sources of diverse, substantially homochiral monomers are profoundly implausible. The presence of a natural and general Table 2: Aspects of anticipated or potential prebiotic conditions, processes, and evolutionary capacity.…”
Section: Racemic Precursors Are Not Problematicmentioning
confidence: 99%
“…Proposed mechanisms that might yield compounds in significant enantiomeric excess (e.g., differential photolysis by circularly polarized starlight [DMMN + 11], the growth and dissolution of chiral crystals [NIM + 08], or hypothetical autocatalytic cycles [GW12]) are of dubious prebiotic realism [ÁBC + 10], while prebiotic sources of diverse, substantially homochiral monomers are profoundly implausible. The presence of a natural and general Table 2: Aspects of anticipated or potential prebiotic conditions, processes, and evolutionary capacity.…”
Section: Racemic Precursors Are Not Problematicmentioning
confidence: 99%
“…Molecular chirality in amino acids, peptides, or proteins is essentially critical as they are the structural and functional basis of the organism ( Kondepudi and Nelson, 1985 ; Mason, 1986 ; Goldanskii and Kuzmin, 1988 ; Campbell, 1990 ; Bonner, 1991 ; Chelaflores, 1994 ; Friedman, 1999 ). In recent years, in addition to the chirality at the molecular level, the effects of the chirality of the supramolecular structures of proteins and peptides are attracting increasing attention due to discoveries of a series of extraordinary phenomenon ( Gutman et al, 1988 ; Surewicz and Mantsch, 1988 ; Fassihi, 1993 ; Boyd et al, 2011 ; Caglioti et al, 2011 ; Taniguchi et al, 2011 ; Gleiser and Walker, 2012 ; Ariga et al, 2020 ). For example, it has been found that the chirality of peptide nanofibers in hydrogel could affect cell adhesion and proliferation ( Das et al, 2013 ; Liu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, different hypotheses on the possible mechanisms of prebiotic, or primordial, chirality amplification were put forward and criticized from different perspectives [2,5,[16][17][18][19][20][21][22]. This contribution is aimed at considering the models relying on far-from-equilibrium chemical mechanisms of enantiomeric enrichment, essentially leaving to separate discussions crystallization-induced chirality amplifications [23], typically considered in connection with the "chance" paradigm [9].…”
Section: Introductionmentioning
confidence: 99%